Damage in fruits of mahogany caused by Hypsipyla grandella (Zeller) (Lepidoptera: Pyralidae) in Brasília, Brazil - de Castro, Marcelo Tavares; Montalvão, Sandro Coelho Linhares; Monnerat, Rose Gomes (EntomoBrasilis, 2018)
Abstract. This study aimed to evaluate qualitatively and quantitatively the Hypsipyla grandella (Zeller) damage in fruits of mahogany in Brasilia, Brazil. For this, fruits were collected and the analysis of each fruit was carried out by assessing the following parameters: fruit weight, fruit length and height, number of holes in fruits characteristic of H. grandella attack, size of the holes, number of larvae and pupae of H. grandella, number of seeds damaged and presence of other insects within the fruit. As a result, 190 (95%) had holes made by the larvae, used primarily for their entry and for exit later as an adult. Most of the fruits showed only a single hole (81%), but up to 5 holes were found in a single fruit. A single caterpillar can feed on various seeds, causing major damage when they attack together. Seventy-two (36%) fruits had all the seeds damaged by H. grandella, especially those containing pupae. 183 larvae in different instars and 45 pupae were found. Only five caterpillars were found dead inside of fruit, representing 2.78% of the caterpillars. Danos em frutos de mogno causados pela Hypsipyla grandella (Zeller) (Lepidoptera: Pyralidae) em Brasília, Brasil Resumo. Este trabalho teve como objetivo avaliar qualitativamente e quantitativamente os danos provocados por Hypsipyla grandella (Zeller) em frutos de mogno em Brasília, Brasil. Para isso, frutos foram coletados e os seguintes parâmetros foram analisados: peso, comprimento, número de orifícios causados pela H. grandella, número de sementes danificadas e presença de outros insetos no interior dos frutos. Como resultado, 190 (95%) frutos apresentaram orifícios feitos pela lagarta, usados primordialmente para sua entrada e posteriormente para a saída, quando adulto. A maioria dos frutos apresentou apenas um orifício (81%), mas até cinco furos foram encontrados em um único fruto. Uma única lagarta pode se alimentar de várias sementes, causando grandes danos. Setenta e dois frutos (36%) tinham todas as sementes danificadas por H. grandella, especialmente aqueles que apresentaram pupas. 183 lagartas em diferentes estádios e 45 pupas foram encontradas. Apenas cinco lagartas foram encontradas mortas dentro dos frutos, representando 2,78% do total.